2019
DOI: 10.1021/acs.cgd.9b01338
|View full text |Cite
|
Sign up to set email alerts
|

(3-Phenylpyridin-1-ium)SbI4: Coulomb Interaction-Assembled Lead-free Hybrid Perovskite-like Semiconductor

Abstract: The environmental toxicity of Pb in inorganic–organic hybrid perovskite presents a major hurdle to commercialization, which has triggered intense research on exploring Pb-free alternatives. Soft interaction, especially Coulomb interaction not only enriching the synthesis strategy but endowing a unique property to the derived materials, is appealing for constructing Pb-free alternatives; however, less has been reported. We herein demonstrate the construction of a Sb-based hybrid perovskite-like semiconductor (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…All these mean that weak hydrogen bonds and Coulomb interaction are mainly responsible for the self-assembly of the crystalline hybrid structure. 37 The most promising structural feature of EtbtBi 2 I 10 is the dimeric (Bi 2 I 10 ) 4− anion surrounded by hydrogen-bond-free Etbt cations, where the N donors bond with hydrophobic alkyl to avoid forming strong hydrogen bonds with external H 2 O. This feature guarantees that EtbtBi 2 I 10 possesses excellent stability at ambient condition and remains in dynamic equilibrium in acid solution.…”
Section: Resultsmentioning
confidence: 99%
“…All these mean that weak hydrogen bonds and Coulomb interaction are mainly responsible for the self-assembly of the crystalline hybrid structure. 37 The most promising structural feature of EtbtBi 2 I 10 is the dimeric (Bi 2 I 10 ) 4− anion surrounded by hydrogen-bond-free Etbt cations, where the N donors bond with hydrophobic alkyl to avoid forming strong hydrogen bonds with external H 2 O. This feature guarantees that EtbtBi 2 I 10 possesses excellent stability at ambient condition and remains in dynamic equilibrium in acid solution.…”
Section: Resultsmentioning
confidence: 99%
“…In comparison with the “hard interaction” typically referring to a coordination bond, which has strong bonding energy, the “soft interaction” is diverse including a hydrogen bond, halogen bond, van der Waals interaction, and Coulomb interaction, which show weak bonding energy. The variety of soft interactions has provided plentiful synthesis strategies toward OHSs with unique structures and properties, and has attracted substantial attention. However, probably due to the directionlessness, therein the Coulomb interaction is relatively difficult to modulate and hitherto is seldom employed as the main force to construct OHSs. , …”
Section: Introductionmentioning
confidence: 99%
“…29−35 However, probably due to the directionlessness, therein the Coulomb interaction is relatively difficult to modulate and hitherto is seldom employed as the main force to construct OHSs. 36,37 As a continuation of our research on the exploration of hypotoxicity OHSs assembled by soft interactions between inorganic and organic moieties, herein the in situ formed 3methylbenzo[d]thiazol-3-ium (Mebti) was first employed to combine with inorganic copper iodide to form a new Cu-OHS, namely, (3-methylbenzo[d]thiazol-3-ium) 2 Cu 3 I 5 (denoted as Mebti-Cu 3 I 5 ). Mebti-Cu 3 I 5 contains a rarely reported onedimensional (1D) (Cu 3 I 5 ) 2− anionic chain formed by the edge sharing (CuI 4 ) tetrahedrons and (CuI 3 ) plane triangles.…”
Section: Introductionmentioning
confidence: 99%
“…Organic–inorganic hybrid metal halide materials have attracted extensive attention as semiconductor materials with exceptional structure and adjustability of luminescent properties, including high absorption coefficient, high electron–phonon coupling coefficient, and high photoluminescence quantum yield (PLQY), which have a wide variety of optoelectronic applications, such as lasers, light-emitting diodes, thin-film transistors, etc. Lead-based metal halide hybrids are usually used to understand luminescent materials with their high PLQY and tunable optical properties. However, the lack of structural stability resisting long-term light, moisture, or high temperature and heavy metal lead toxicity to humans and the environment all limit its further real applications. To overcome these problems, it is indispensable to obtain environmentally friendly stable organic–inorganic hybrid metal halide materials. Generally, using other inorganic materials instead of toxic lead materials and lowering the structural dimension can greatly reduce the toxicity and improve the stability, respectively. For instance, Xia et al reported that the 0D hybrid material of (C 8 H 14 N 2 ) 2 SnBr 6 shows excellent photostability under 80 min of continuous ultraviolet light irradiation, and the integrated intensity remained above 90% of the initial stage .…”
mentioning
confidence: 99%